"It's important to me": A qualitative analysis on shared decision‐making and patient preferences in older adults with early‐stage breast cancer. Issue 2 (22nd September 2020) - Lawhon, Valerie M.; England, Rebecca E.; Wallace, Audrey S.; Williams, Courtney P.; Williams, Beverly R.; Niranjan, Soumya J.; Ingram, Stacey A.; Rocque, Gabrielle B.
Abstract: Objective: Shared decision‐making (SDM) occurs when physicians and patients jointly select treatment that aligns with patient care goals. Incorporating patient preferences into the decision‐making process is integral to successful decision‐making. This study explores factors influencing treatment selection in older patients with early‐stage breast cancer (EBC). Methods: This qualitative study included women age ≥65 years with EBC. To understand role preferences, patients completed the Control Preferences Scale. Semi‐structured interviews were conducted to explore patients' treatment selection rationale. Interview transcripts were analyzed using a constant comparative method identifying major themes related to treatment selection. Results: Of 33 patients, the majority (48%) desired shared responsibility in treatment decision‐making. Interviews revealed that EBC treatment incorporated three domains: Intrinsic and extrinsic influences, clinical characteristics, and patient values. Patients considered 19 treatment selection themes, the most prioritized including physician trust and physical side effects. Conclusions: Because preferences and approach to treatment selection varied widely in this sample of older, EBC patients, more research is needed to determine best practices for preference incorporation to optimize SDM at the time of treatment decisions.